Ultrastructural changes in renal tissue in rats with renal failure under the influence of herbal composition BNO 2103 - V. V. Chernykh; К. О. Zupanets; S. K. Shebeko (Zaporozhye State Medical University, 2022)
Management of chronic kidney disease is an urgent task of the global health care system, as untreated, it leads to partial or permanent loss of kidney function. Standardized herbal remedies are highly effective and relatively safe. That is why it is suggested to pay attention to herbal remedies already known for the treatment of genitourinary diseases to expand the indications for their use. The aim of the research is to study the nephroprotective properties of the standardized herbal composition BNO 2103, which is the active ingredient of Canephron N ®, in a model of renal failure in rats. Materials and methods. An experimental study was performed on 42 male white outbred rats weighing 150-200 g, which were divided into 4 groups. Nephropathy was induced by a single subcutaneous injection of 0.7 ml/kg of 2.5 % potassium chromate solution. Animals in 3 and 4 groups received BNO 2103 at a dose of 33.0 mg/kg and prednisolone at a dose of 1.9 mg/kg intragastrically daily for 20 days. After animals were sacrificed, their kidneys were obtained and studied with standard electronic microscopy methods. Results. BNO 2103 normalized the ultrastructural picture of the kidneys, however, with the presence of minor pathological signs. BNO 2103 reduced the destruction of basement membranes, improved organelle structure and increased metabolic processes in podocytes, and endotheliocytes, reducing the manifestations of degenerative-dystrophic changes in them. BNO 2103 was superior to the reference drug prednisolone. Conclusions. BNO 2103 showed a significant nephroprotective effect, normalizing the ultrastructural picture of the kidneys in rats with renal failure. This effect is most likely related to the presence of biologically active substances with a powerful antioxidant, anti-inflammatory, nephroprotective activity. The obtained results allow us to consider BNO 2103 as a promising nephroprotective agent for the treatment of chronic kidney disease.